Carbon microsphere derived from pomegranate peels: turn-on fluorescent and smartphone-assisted sensor for direct detection of H2O2 - Hamidreza Seyedbarai; Negar Alizadeh; Abdollah Salimi (Results in Chemistry)
The measurement of hydrogen peroxide (H₂O₂) is vital in environmental monitoring, biomedical applications, and industrial processes. This study presents a novel method for synthesizing carbon microspheres (CMs) from pomegranate peels, which serve as a turn-on fluorescence and colorimetric probe for direct H₂O₂ detection. The synthesis involves adding ammonia to powdered pomegranate peel at room temperature, resulting in a color change from red to brown. Upon H₂O₂ addition, the solution transitions from brown to yellow and ultimately to colorless, with a significant increase in fluorescence observed. Fourier-transform infrared (FTIR) and Raman analyses confirm that H₂O₂ induces oxidation of the microspheres, enhancing their fluorescence. The probe exhibits a wide linear range of 0.5–750 μM and a low detection limit of 83 nM, making it suitable for environmental and biomedical applications. Additionally, the color change of the carbon microspheres can be measured using a smartphone colorimetric method, with a detection range of 1 to 1000 μM. This work highlights the potential of utilizing agricultural waste, specifically pomegranate peels, to develop sustainable materials for advanced sensing technologies.